THE USE OF THE NUMBER FORMS OF NOUNS IN ENGLISH AND ROMANIAN - Nicoleta Florina Mincă (Studii de gramatică contrastivă, 2019)
The paper presents the use of the number forms of nouns in English and Romanian. In English, there are regular and irregular nouns. The plural of some abstract and material nouns may be used to express intensity, great quantity and extent. The stem of an English noun can be used attributively, or in a collective sense. In Romanian, the number opposition of nouns is marked by desinences. There are some nouns which have double forms of the same gender in the singular, and there are nouns which have two or three forms in the plural. Certain Romanian nouns have only one form, either of singular - singularia tantum, or of plural - pluralia tantum. The collective nouns are those denoting a plurality of objects regarded as a single whole.